Project MinE: study design and pilot analyses of a large-scale whole-genome sequencing study in amyotrophic lateral sclerosis - Hardiman, Orla; Mc Laughlin, Russell (Springer Nature, 2018)
The most recent genome-wide association study in amyotrophic lateral sclerosis (ALS) demonstrates a disproportionate contribution from low-frequency variants to genetic susceptibility to disease. We have therefore begun Project MinE, an international collaboration that seeks to analyze whole-genome sequence data of at least 15 000 ALS patients and 7500controls. Here, we report on the design of Project MinE and pilot analyses of successfully sequenced 1169 ALS patients and608 controls drawn from the Netherlands. As has become characteristic of sequencing studies, we find an abundance of rare genetic variation (minor allele frequency < 0.1%), the vast majority of which is absent in public datasets. Principal component analysis reveals local geographical clustering of these variants within The Netherlands. We use the whole-genome sequence data to explore the implications of poor geographical matching of cases and controls in a sequence-based disease study and to investigate how ancestry-matched, externally sequenced controls can induce false positive associations.Also, we have publicly released genome-wide minor allele counts in cases and controls, as well as results from genic burden tests.
Keywords: Amyotrophic lateral sclerosis (ALS); Genome-wide association study; Rare genetic variation